SMEs and exogenous shocks: A conceptual literature review and forward research agenda. (March 2022) - Miklian, Jason; Hoelscher, Kristian
Economic crises, natural disasters, armed conflict and infectious disease outbreaks, amongst others, present interlinked challenges for small businesses and have generated a recent wealth of research across varied fields. Therefore, this article outlines an analytical lens suggesting how SMEs experience shocks and crises that focuses on the interlinked nature of (i) the business, (ii) the shock and (iii) the response within a given context. We thematically draw out key trends, knowledge gaps and tensions and highlight promising research and engagement avenues for future scholarship and practice. We contextualise (i) how small businesses are distinct from large firms in how they experience shock and crisis events; (ii) how different types of crises impact small business; (iii) how shocks and crises shape SME-specific responses and (iv) how the COVID-19 pandemic as a 'novel exogenous shock' influences all of the above. We conclude by emphasising emerging knowledge avenues for future small business, shock and crisis research.